The reading of tajweed in surah Yaasin for red-green colour vision deficiencies / Siti Sarah Adam Wan … [et al.] - Adam Wan, Siti Sarah; Harun, Azahar; Abdulah, Nur Hasliza; Dasuki, Shaliza (2017)
Colour Blindness or colour vision deficiency are difficulty to see certain colour and shade depending on their type of colour blindness. Generally, there are 3 types of vision deficiencies - protanopia (red-green), deuteranopia (green-red) and tritanopia (blue-yellow) (NEI, 2015). There are close to 300 million people around the world who are suffering from colour blindness. From that figure, 8% men and 0.5% women are suffering this vision deficiencies (Ng, 2017). Many people think people who are suffering from colorblindness are enable to see any colours. Their perception on those people can only view black and white in daily life. However, their judgment is wrong and science has proven colour vision deficiencies can see colours (Flück, 2006). Most common forms of colour vision problems are inherited (genetic) and are present at birth.However,in some cases, a person can have an acquired colour vision problem. Thus,it is caused by aging, eye problem, injury on eye, alcohol misuse, or a hard injury on head (Flück, 2006).